Selective Fluorescence Quenching Sensor for Trace Determination of Iron (Fe2+/Fe3+) in Water Sample Using Natural Carbon Dots (CDs) Synthesized by Microorganisms from Leech Lime (Citrus hystrix DC.) Fermentation Extract - Janshongsawang, Jirapat; Pimsin, Nipaporn; Nugroho, David; Nuengmatcha, Prawit; Porrawatkul, Paweena; Chanthai, Saksit (Trends in Sciences, 2025)
This study presents a green and low-cost fluorescence sensing platform for the simultaneous detection of Fe²⁺ and Fe³⁺ ions (total iron) in water using carbon dots (CDs) synthesized via natural fermentation of Citrus hystrix DC. (leech lime) fruit. The hypothesis is that functional groups on the surface of biosynthesized CDs can selectively coordinate with both iron oxidation states, resulting in effective fluorescence quenching. The CDs were characterized using UV-Vis spectroscopy, fluorescence spectroscopy, FTIR and TEM, confirming their spherical morphology and strong blue emission at 454 under 330 nm excitation. Experimental optimization was performed for key sensing parameters, including pH, ionic strength (NaCl), EDTA concentration, reaction time and temperature. Under optimized conditions (pH 4, 5 mM EDTA, 0.1 M NaCl, 50 °C, 10 min reaction), a linear fluorescence quenching response was observed in the 30 - 100 µM total iron range, with a limit of detection (LOD) of 8.05 µM and limit of quantification (LOQ) of 26.85 µM. The method demonstrated high selectivity toward iron ions over 20 other metal ions and negligible interference from chloride and carbonate. Recovery tests in drinking and tap water samples yielded values between 86.65% - 115.06%, validating the method’s applicability for real-world water monitoring. This work highlights the potential of naturally derived CDs as effective and environmentally sustainable probes for trace iron analysis in environmental samples. HIGHLIGHTS The carbon dots were successfully synthesized from leech lime fermentation extract. Selective fluorescence sensor for iron determination was successfully optimized. The developed sensing probe is a good method for the Fe2+/Fe3+ detection. GRAPHICAL ABSTRACT